Electroconvulsive therapy modulates loudness dependence of auditory evoked potentials: a pilot MEG study - Dib, Michael; Lewine, Jeffrey David; Abbott, Christopher C.; Deng, Zhi-De (Frontiers in Psychiatry, 2024)
Electroconvulsive therapy (ECT) remains a critical intervention for treatment-resistant depression (MDD), yet its neurobiological underpinnings are not fully understood. This pilot study utilizes high-resolution magnetoencephalography (MEG) in nine depressed patients receiving right unilateral ECT, to investigate the changes in loudness dependence of auditory evoked potentials (LDAEP), a proposed biomarker of serotonergic activity, following ECT. We hypothesized that ECT would reduce the LDAEP slope, reflecting enhanced serotonergic neurotransmission. Contrary to this, our findings indicated a significant increase in LDAEP post-ECT (t 8 = 3.17, p = .013).The increase in LDAEP was not associated with changes in depression severity or cognitive performance, as assessed by the 24-item Hamilton Depression Rating Scale (HDRS 24 ) and Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). We discussed potential mechanisms for the observed increase, including ECT's impact on serotonergic, dopaminergic, glutamatergic, and GABAergic receptor activity, neuroplasticity involving brainderived neurotrophic factor (BDNF), and inflammatory modulators such as TNF-α. Our results suggest a complex interaction between ECT and these neurobiological systems, rather than a direct reflection of serotonergic neurotransmission.